Pengembangan buku panduan bimbingan kelompok dengan teknik problem solving untuk perencanaan karir siswa di sekolah menengah kejuruan - Nofarissa, Aulia; Putri, Dewi Arum Widhayanti Metra; Lestari, Luh Putu Sri (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This research is research development or research and development. The development procedure used in this study uses the 4D model, namely: define, design, development, and dissemination. This study implemented the subject of 3 guidance counseling experts from Universitas Pendidikan Ganesha guidance counselors and 3 guidance counseling experts from counseling teachers at schools. In the process of studying the effectiveness of the guidebook, researchers implemented 10 students of SMK Negeri 3 Singaraja as subjects. Of the 25 items of the instrument which were used to assess content validity, it was stated that the group guidance manual with problem solving techniques for student career planning had good validity in each item. The assessment of the content validity index of the counseling manual is very important to determine whether it is appropriate or not to be used. The hypothesis study explains that the Handbook is effective in enhancing students' career planning. For the ES value = 1.334 which is included in the high ES category.